2022
DOI: 10.3892/ol.2022.13573
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prognosis of gastrointestinal stromal tumors with rare site metastasis (Review)

Abstract: Gastrointestinal stromal tumors (GIST) are the most common stromal-derived tumors of the gastrointestinal tract and have a potential metastatic capacity in almost half of all cases, with the most common sites of metastasis being the liver and peritoneum. However, there is evidence that GIST metastasizes to sites other than the liver and peritoneum, which poses challenges for clinical diagnosis and treatment. Therefore, the Cochrane and Medline databases were searched via PubMed in July 2022 using relevant keyw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 118 publications
0
1
0
1
Order By: Relevance
“…13 There have been rare reports of GIST metastasizing to the ovary. [14][15][16][17] From our study, we found a case of metastasis of GIST to the left ovary. This was in a 54-year-old woman.…”
Section: Discussionmentioning
confidence: 65%
“…13 There have been rare reports of GIST metastasizing to the ovary. [14][15][16][17] From our study, we found a case of metastasis of GIST to the left ovary. This was in a 54-year-old woman.…”
Section: Discussionmentioning
confidence: 65%
“…Extragastrointestinal stromal tumor (eGIST) is extremely rare. Metastasis is common in advanced GIST which usually metastasized to liver (50-65%) and peritoneum (20-43%), and less frequently to lymph node (< 6%), bone (< 6%) and lung (< 2%), with other sites relatively rare [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Частина СПШКТ має доброякісний характер. Можливе метастазування СПШКТ у печінку і очеревину, рідше до м'яких тканин або до кісток, та до легень [9,10]. Казуїстикою є метастазування у лімфатичні вузли (за винятком дитячих СПШКТ та при синдромі Карні-Стратакіса) [6,11].…”
unclassified